Organising undergraduate research projects: student-led and academic-led models. (10th October 2016) - Knight, Rachael-Anne; Botting, Nicola
Abstract : Purpose: The purpose of this paper is to address the management of undergraduate final year research dissertations. It intends to explain and clarify the experience of two models of delivery (student-led/academic-led) with reference to interest development theory (Hidi and Renninger, 2006 ). Design/methodology/approach: The authors focus on the advantages and drawbacks of each model within the context of the research literature, and describe a case study of the experiences of lecturers and students in one division of a metropolitan UK university, running a leading programme in speech and language therapy (pathology). Recommendations are made which are intended to be of use to colleagues across disciplines and organisations. Findings: The authors argue that a delivery where students can choose their research topic from a limited set suggested by supervisors (academic-led model) is best placed to meet motivational challenges in Hidi and Renninger's framework, and also increase feasibility for staff. The authors discuss how such a model might best be implemented. Originality/value: Describing case study experiences within a conceptual framework is important for the development of improved supervision methods. It is hoped that this case study paper will inform other institutions by providing clear theoretical underpinnings and practical recommendations; and that it will lead to further empirical research into models of organising final year dissertations.